The behavior and natural history of Chartergellus, a little-known genus of neotropical social wasps (Vespidae Polistinae Epiponini) - Chavarría-Pizarro, L. [UNESP]; West-Eberhard, M. J. (Taylor & Francis, 2010)
This study reviews published data on the behavior and natural history of Chartergellus and presents the first observations on social interactions in this genus of tropical swarm-founding wasps. Observations of Chartergellus golfitensis in Costa Rica and C. punctatior in Colombia showed that queens perform a post-oviposition egg-guarding vigil, and a bending display like that characteristic of epiponine social wasps that lack consistent morphological differences between workers and queens and have caste determination in the adult stage. Young, old, and queen (egg-laying) females of C. golfitensis showed small differences that indicate color changes with age, and structural differences that could be due to seasonal or colony-cycle changes in developmental conditions, but do not rule out the possibility of pre-adult caste determination, a phenomenon that needs to be carefully distinguished from pre-adult caste bias. Sexual dimorphism and the behavior of males at the nest in C. golfitensis is described, as well as the aggressive and avoidance behavior of females toward males. Nest structure in both species is as described previously for Chartergellus species, but some anomalies and their possible evolutionary significance are discussed. Cell initiation by an egg-laying queen, a behavior never seen by workers, and by a young female with slightly developed ovaries, may be vestiges of ancestral solitary reproductive traits where developed ovaries are associated with cell construction. © 2010 Dipartimento di Biologia Evoluzionistica dell'Università, Firenze, Italia.
Keywords: aggressive displays; caste determination; communication; egg-guarding; nest architecture; reproductive groundplan hypothesis; sexual dimorphism; social selection; aggression; behavioral ecology; caste; comparative study; egg; historical ecology; literature review; morphology; nest structure; oviposition; seasonality; selection; wasp; Colombia; Costa Rica; Epiponini; Polistinae; Vespidae